Expression of FOXP3, CD14, and ARG1 in Neuroblastoma Tumor Tissue from High-Risk Patients Predicts Event-Free and Overall Survival. (16th June 2015) - Stigliani, Sara; Croce, Michela; Morandi, Fabio; Scaruffi, Paola; Rigo, Valentina; Carlini, Barbara; Manzitti, Carla; Gigliotti, Anna Rita; Tonini, Gian Paolo; Pistoia, Vito; Ferrini, Silvano; Corrias, Maria Valeria
Abstract : The prognosis of children with metastatic neuroblastoma (NB) > 18 months at diagnosis is dismal. Since the immune status of the tumor microenvironment could play a role in the history of disease, we evaluated the expression of CD45, CD14, ARG1, CD163, CD4, FOXP3, Perforin-1 ( PRF1 ), Granzyme B (GRMB), and IL-10 mRNAs in primary tumors at diagnosis from children with metastatic NB and tested whether the transcript levels are significantly associated to event-free and overall survival (EFS and OS, resp.). Children with high expression of CD14, ARG1 and FOXP3 mRNA in their primary tumors had significantly better EFS. Elevated expression of CD14, and FOXP3 mRNA was significantly associated to better OS. CD14 mRNA expression levels significantly correlated to all markers, with the exception of CD4 . Strong positive correlations were found between PRF1 and CD163, as well as between PFR1 and FOXP3 . It is worth noting that the combination of high levels of CD14, FOXP3, and ARG1 mRNAs identified a small group of patients with excellent EFS and OS, whereas low levels of CD14 were sufficient to identify patients with dismal survival. Thus, the immune status of the primary tumors of high-risk NB patients may influence the natural history of this pediatric cancer.